Analysis of the morbidity of residents of Belarus who received thyroid exposure due to the accumulation of I-131 during fetal development as a result of the accident at the Chernobyl nuclear power plant - Khrustalev, Vladislav; Stojarov, Alexander (Journal of the Belarusian State University. Ecology, 2023)
Analysis of the cohort of individuals living in the Stolin district of the Brest region, who received exposure during prenatal development due to the accumulation of I-131 in the thyroid gland, has shown that both the general morbidity and the morbidity of the nervous, cardiovascular, genitourinary systems, and also of the gastrointestinal tract, are increased and differs from the incidence in individuals, identical in a number of parameters, who were not exposed to radioactive iodine in utero. The study cohort was dominated by relatively small doses to the thyroid gland, not exceeding 30 mGy. And only 10 % of the irradiated doses were about 100 mGy. In the group of children irradiated in utero with I-131 in subsequent years, a linear incidence rate for mental and behavioral disorders (Chapter V according to ICD-10) is observed, which is almost three times higher than in the group of non-irradiated individuals. Approximately the same dependence can be observed in the group of diseases of the nervous system (Chapter VI). The frequency of diseases of the circulatory system (Chapter IX) in the main group was approximately 2.5 times higher than in the control group. In a cohort of children who were exposed to I-131 in utero, the incidence of diseases of the genitourinary system (Chapter XIV) was noted throughout the entire observation period, i.e. until 2017 and was increased by about 4 times. The appearance of the pathology was delayed, and it has started to manifest 10 years after the Chernobyl accident. In most cases, the incidence in the group of non-exposed persons had a sigmoid dependence and reached a plateau without further increase. In contrast, in the group of exposed victims, the incidence tends to increase. The observed data may be explained by the variable sensitivity of certain genes of the thyroid tissue to radiation. They might become up- or downregulated and lead to an altered thyroid hormone background, which affected all body systems without exception, subsequently causing the appearance of multiple pathology.